Paradigma da complexidade: uma leitura semiológica (Significação: Journal of Audiovisual Culture, 2005)
Edgar Morin's complexity’s paradigm seems to have opened new windows to knowledge production. Its comprehension passes, among other things, to its signs dialogue. It is what this essay pretends, in a temporary sense, by semiology, of Roland Barthes, contemplating some cultural and philosophical aspects.